2013
DOI: 10.1097/brs.0b013e318270b243
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated With Inferior Results After Surgery for Lumbar Spinal Stenosis

Abstract: Obese patients achieved significant pain reduction, better walking ability, and improved quality of life after surgical treatment of LSS. Nevertheless, obesity was associated with a higher degree of dissatisfaction and poorer outcomes after surgery for LSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 61 publications
7
91
0
3
Order By: Relevance
“…In a large-registry study of 2633 lumbar stenosis patients, obese patients, in general, had less satisfaction following surgery. 13 However, in a study by McGuire and colleagues, there was no difference between obese and nonobese patients in symptom satisfaction at 12 months following surgery specifically for degenerative lumbar spondylolisthesis. 17 It is important to note that in our multivariate analysis, when adjusting for potential confounders, BMI was not a significant independent predictor of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large-registry study of 2633 lumbar stenosis patients, obese patients, in general, had less satisfaction following surgery. 13 However, in a study by McGuire and colleagues, there was no difference between obese and nonobese patients in symptom satisfaction at 12 months following surgery specifically for degenerative lumbar spondylolisthesis. 17 It is important to note that in our multivariate analysis, when adjusting for potential confounders, BMI was not a significant independent predictor of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that high patient satisfaction may be correlated with efficient and high-quality surgical care 28 and superior surgical outcomes. 20 Authors investigating lumbar spine surgery have specifically linked various patient characteristics to satisfaction, including smoking, depression, disability-derived unemployment, 4 sex, 9 obesity, 13 preoperative diagnosis, 7 payer status, worse baseline pain and disability scores, 6 and psychological comorbidity.…”
mentioning
confidence: 99%
“…In the present study, obese patients were more likely to require a decompression, which is consistent with previous studies that suggested obesity is a risk factor for spinal stenosis. 21,34,67 …”
Section: Discussion Patient Demographic Datamentioning
confidence: 99%
“…45,65,75 Similarly, there is no consensus on the impact of BMI on patient-reported outcomes. Several authors have reported inferior postoperative outcomes in obese patients undergoing elective degenerative lumbar, cervical, and deformity surgery, 2,34,76 whereas others did not find that obesity negatively impacts measures of health-related quality of life (HRQL). 15,26,53,70 In the spinal deformity literature, a publication by Smith et al identified high BMI as a risk factor for worse postoperative outcomes in both older and younger ASD patients undergoing surgical treatment.…”
mentioning
confidence: 99%
“…These studies infer, that although specific disease characteristics pertaining to LSS may have a predictive value, psychosocial and demographic parameters are usually even more associated with the outcome of surgery (Sinikallio et al 2009;Atlas et al 2010;Cobo Soriano et al 2010;Pearson et al 2012). Additional factors of importance, as shown by data from the Swedish Spine Register, are smoking and obesity (Sandén et al 2011;Knutsson et al 2013). …”
Section: Outcome Of Surgery For Lumbar Spinal Stenosismentioning
confidence: 99%